2002
DOI: 10.1200/jco.2002.20.1.160
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Oral Capecitabine in Patients With Advanced or Metastatic Pancreatic Cancer

Abstract: Treatment with capecitabine resulted in clinically significant beneficial effects on tumor-related symptoms and yielded objective response activity in patients with metastatic or locally advanced pancreatic cancer. These results together with its generally tolerable safety profile and the added advantage of oral administration provide the basis for further evaluating capecitabine as a single agent or in combination with other treatment modalities in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Compared to these administration approaches, oral administration has its own advantages. It is safer, more convenient, and more tolerable for patients (48). OP-D is a saponin containing several glycosidic bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to these administration approaches, oral administration has its own advantages. It is safer, more convenient, and more tolerable for patients (48). OP-D is a saponin containing several glycosidic bonds.…”
Section: Discussionmentioning
confidence: 99%
“…It has proved to be active for therapy in PDAC 21. Thus, a combination of capecitabine and oxaliplatin (XELOX) is also expected to be as effective as the combination of 5-FU and oxaliplatin, used as a second-line regimen for PDAC patients whose cancers have progressed after treatment with a gemcitabine-based regimen.…”
Section: Introductionmentioning
confidence: 99%
“…For decades, 5-FU has been the only drug displaying even a glimmer of activity [57][58][59]. More recently, the 5-FU prodrug, capecitabine, evoked a 25% clinical benefit response and a 7.3% objective response [60]. However, with the development of gemcitabine, clinical trials suggested an improvement in both quality of life and survival of patients receiving this drug despite a relatively low objective response rate of only 5% [61•,62].…”
Section: Systemic Chemotherapymentioning
confidence: 99%